Navigators of Dune [compact disc, unabridged] - Herbert, Brian (Macmillan Audio, 2016)
Set 10,000 years before Frank Herbert's classic Dune, the story tells the origins of the Bene Gesserit Sisterhood and its breeding program, the human-computer Mentats, and the Navigators, as well as a crucial battle for the future of the human race, in which reason faces off against fanaticism. These events have far-reaching consequences that will set the stage for Dune, millennia later.